International practices, beliefs and values in not-for-profit financial reporting. Issue 1 (2nd January 2019) - Cordery, Carolyn J.; Crawford, Louise; Breen, Oonagh B.; Morgan, Gareth G.
ABSTRACT: Financial reporting is an important aspect of not-for-profit organisations' (NPOs') discharge of accountability, particularly for donations and funding. Nevertheless, NPO financial reporting lacks a global approach. Drawing on a multi-national study this paper utilises a pattern-matching methodology to capturing institutional logics. We uncover tension between NPO financial reporting practice (underpinned by symbolic and material carriers of a local financial reporting logic), and a majority believe that NPO international financial reporting standards should be developed and followed. Conflict between local practice and stakeholder beliefs is evident. Significant belief differences across key stakeholder groups will likely impact the NPO financial reporting development. HIGHLIGHTS The call for international standards for financial reporting for not-for-profit entities is strongly supported. Yet this project is beset by contested logics in respect of notions of the purpose of financial reporting, comparability and how reports should be prepared. Beliefs that powerful regulators and legislators are likely influential agents for internationalising NPO financial reporting change, conflict with notions that individual nations can effect change.